Pengaruh Latihan Skipping Terhadap Kecepatan Tendangan pada Cabang Olahraga Karate SMAN 1 Sooko - Tedi Saputra; Purbodjati (Indonesian Journal of Kinanthropology (IJOK), 2021)
Background: This study aims to determine the effect of skipping exercise on kick speed in karate at SMAN 1 SOOKO. Methods: This research is a quantitative descriptive research using statistics from two variables, namely: Skipping Exercise and Kick Speed. The population in this study was 25 people of karate athletes at SMAN 1 SOOKO (15 boys and 10 girls). Theproportional sampling technique because the researcher got advice from the coach with a sample of 14 people consisting of 7 male and 7 female karate athletes at SMAN 1 SOOKO. Results: Based on the results of this study, it can be concluded that there is an effect of skipping exercise on kick speed) in karate at SMAN 1 SOOKO (Mean = 141.50). Conclusions: Based on the results of the research and discussion in the description above, it can be concluded that there is an effect of skipping exercise on the speed of the athletes of SMAN 1 SOOKO X.1, X.2 and Y.1, Y.2 results (Mean = 141.50 and 40.0 ). Researchers recommend doing skipping exercises for 2 meetings/week to increase athlete's strength.